(3GdYeOI aj GdCMcGe ef MOjK GdfHi Ydjg GdUdGI hGdSdGes - (3Jbi GdOjf CHi eMeO YHO GdZfj Hf YHO GdhGMO Hf Ydj GdLeGYjdi GdebOSis ((3CUagGf s)
(3ChdgG (B:s
(3GdMeO ddg Gdedc GdLHGQ GdhGMO GdbgGQ CeG HYO aEf HYV ENhGfi SCdfi GNJUGQ LedI s
(3BNQgG (B:s
(3Yf LGHQ QLd ef GdCfUGQ ZdGekG dg aHGYg HKeGfeGFI OQge Ke CQSd Kefg Edjg Je cJGH GdYeOI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B164 - (3U(B219s
(3GdfSNI HgG MhGTs
(3HGdfSNI cdeGJ HGdRQbI hGdMeQI hGdePgHs
(3Ydi GdfSNI JbjjOGJ cKjQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs